Anastomotic Techniques and Associated Morbidity in Total Minimally Invasive Transthoracic Esophagectomy: Results From the EsoBenchmark Database. Issue 5 (November 2019) - Schröder, Wolfgang; Raptis, Dimitri A.; Schmidt, Henner M.; Gisbertz, Suzanne S.; Moons, Johnny; Asti, Emanuele; Luyer, Misha D. P.; Hölscher, Arnulf H.; Schneider, Paul M.; Henegouwen, Mark I. van Berge; Nafteux, Philippe; Nilsson, Magnus; et al.
Abstract : Objective: The aim of this study was to describe anastomotic techniques used for total minimally invasive transthoracic esophagectomy (ttMIE) and to analyze the associated morbidity. Background: ttMIE faces increasing application in surgical treatment of esophageal cancer. For esophagogastric reconstruction, different anastomotic techniques are currently used, but their effect on postoperative anastomotic leakage and morbidity has not been investigated. Patients and Methods: Patients were selected from a basic dataset, collected during a 5-year period from 13 international surgical high-volume centers. Endpoints were anastomotic leakage rate and postoperative morbidity in correlation to anastomotic techniques, measured by the Clavien-Dindo classification and the Comprehensive Complication Index (CCI). Results: Five anastomotic techniques were identified in 966 patients after ttMIE: intrathoracic end-to-side circular-stapled technique in 427 patients (double-stapling n = 90, purse-string n = 337), intrathoracic (n = 109) or cervical (n = 255) side-to-side linear-stapled, and cervical end-to-side hand-sewn (n = 175). Leakage rates were similar in intrathoracic and cervical anastomoses (15.9% vs 17.2%, P = 0.601), but overall complications (56.7%% vs 63.7%, P = 0.029) and median 90-day CCI 21 [interquartile range (IQR) 0–36] vs 29 [IQR 0–40], P = 0.019 favored intrathoracic reconstructions. Leakage rates after intrathoracic end-to-side double-stapling (23.3%) and cervical end-to-side hand-sewn (25.1%) techniques were significantly higher compared with intrathoracic side-to-side linear (15.6%), end-to-side purse-string (13.9%), and cervical side-to-side linear-stapled esophagogastrostomies (11.8%) ( P < 0.001). Multivariable analysis confirmed anastomotic technique as independent predictor of leakage after ttMIE. Conclusion: Results of this analysis present the current status of the technical evolution of ttMIE with anastomotic leakage as predominant surgical complication. However, technique-related morbidity requires cautious interpretation considering the long learning curve of this complex surgical procedure.